The Role of Housing and Settlement Areas Department of Gayo Lues Regency in the Implementation of a Healthy Housing Environment for the Community of Kutapanjang District - Matondang, Emmil Mohd Arief; Isnaini, Isnaini; Adam, Adam; Sinaga, Rudi Salam (Budapest International Research and Critics University, 2021)
The Government of Gayo Lues Regency needs to create a healthy housing environment for the people of Kutapanjang District so that the predicate as a slum area does not grow. One of the efforts is to create a healthy housing environment through the livable housing program. This study aims to describe the role of the Perkim Office of Gayo Lues Regency in implementing a healthy housing environment for the people of Kutapanjang District through the habitable housing program. Problems in implementing the livable housing program are complex. This is due to various obstacles, such as: 1) lack of coordination between existing SKPKs; 2) The minimum amount of available budget; and 3) the existence of nepotism/proximity factor in program implementation and participating activities become obstacles in its implementation. This research uses the theory of Biddle and Thomas. The method used is qualitative research, where data collection techniques are through observation, interviews and documentation studies. The results of this research indicate that the role of housing and settlement areas department of gayo lues regency in the implementation of a healthy housing environment for the community of Kutapanjang District has not run optimally